Advances in columnar flotation - Azañero Ortiz, Ángel (2003)
Column flotation is particularly attractive for applications involving multiple cleaning stages in conventional cells and for complex minerals that have selectivity problems, substantially raising the grade of the concentrate (2-4%) and higher recovery (2-3%) , with a single cleaning stage, this equipment adapting very well to computer control. Its acceptance in the mining industry is increasing due to multiple advantages including lower cost of installation and operation, less space occupation, substantial decrease in energy consumption, mainly because it does not have a mechanical agitation system, and less consumption of reagents.